A Systematic Review of Psychometric Properties of Health-Related Quality-of-Life and Symptom Instruments in Adult Acute Leukemia Survivors. Issue 5 (September 2016) - Bryant, Ashley Leak; Walton, AnnMarie; Shaw-Kokot, Julia; Mayer, Deborah K.; Reeve, Bryce B.
Abstract : Background: Acute leukemia represents 4% of cancer cases in the United States annually. There are more than 302 000 people living with acute and chronic leukemia in the United States. Treatment has been shown to have both positive and negative effects on health-related quality of life (HRQOL). Objective: The aims of this study were to examine psychometric properties of symptom and HRQOL instruments and to provide implications for the assessment in adults with acute leukemia relevant to clinical practice and future research. Methods: Systematic literature search was conducted from 1990 to 2014 using electronic databases and manual searches. Psychometric studies were considered eligible for inclusion if (1) the psychometric paper was published using at least 1 HRQOL or symptom instrument, and (2) adults with acute leukemia were included in the sample. Studies were excluded if the age groups were not adults, or if the instrument was in a language other than English. Results: Review identified a total of 7 instruments (1 cancer generic HRQOL, 2 symptom related, 3 HRQOL combined with symptom questions, and 1 disease specific). The most commonly used instrument was the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30, followed by the Functional Assessment of Cancer Therapy–Fatigue. Conclusions: An acute leukemia diagnosis can have a significant impact on HRQOL. Our recommendations include using both an HRQOL and symptom instrument to capture patient experiences during and after treatment. Implications for Practice: The availability of comprehensive, valid, and reliable HRQOL and symptom instruments to capture the experiences of adults with acute leukemia during and after treatment is limited.